Osteoinductive effect of rosuvastatin, simvastatin and atorvastatin in Dentistry (Research, Society and Development, 2022)
This exploratory integrative review study aims to describe the effectiveness of the use of lipid-lowering agents in alveolar bone regeneration in Dentistry. For this, descriptors registered in Descriptors in Health Sciences (DeCS) and Medical Subject Headings (MeSH) were applied in the Online System of Search and Analysis of Medical Literature (MEDLINE) through PubMed, in addition to Google Scholar, Brazilian Bibliography of Dentistry (BBO) and Latin American and Caribbean Literature in Health Sciences (LILACS). Initially, 1,721 studies were found and, after a thorough analysis of titles and abstracts and evaluation of the eligibility criteria adopted, 17 clinical trials were included in this study. Rosuvastatin, simvastatin and atorvastatin showed promise in the process of bone regeneration in periodontics, oral surgery and implantology, with India being the country with the most research in this field (n = 14). Most studies (n=14) evaluated the effect of drugs associated with root planing in chronic periodontitis. The concentration of 1.2% of lipid-lowering agents was the most frequent in the selected trials (n=13). Two studies showed non-significant values of increase in bone structure when administered alone. Statins are a promising therapy in some specialties of dentistry. However, it is suggested that further studies in the area with larger samples and longer periods be carried out in order to better elucidate the drug treatment with such drugs in dental practice.